Incidence of Milk Fever on Dairy Cows and Its Risk Factors in Gondar Town, Northwest Ethiopia - Anteneh, S; Guadu, T; Fentahun, T; Chanie, M (International Journal of Natural Sciences, 2013)
The study was conducted on 384 dairy cows in Gondar town during October, 2009 to January, 2010 to determine the prevalence of milk fever and risk factors associated with the disease. Data was collected using regular farm visits, clinical examination of periparturient cows and response to treatment. The overall prevalence of milk fever was 30.2%. Milk fever was significantly associated with milk yield (p<0.05), parity (p<0.05) and breed (p<0.05). Cows with <25, 25-30 and >30 liters of milk per day per cow had 21.83%, 22.4%and 50.92% milk fever respectively. The occurrence of milk fever was 17%, 17% and 73.3% in cows with <3, 3-4 and ? parities. The prevalence was higher (p<0.05) in >50% Friesian blood and 50%Friesian blood cows. Seventy five percent of the cows showed variable response to treatment with Calcium borogluconate, 16.37% did not respond and died and the remaining 8.62% of cows died due to lack of treatment. From these results, milk fever appear to be a big problem in Gondar dairy farms while milk yield, parity and breed are the associated risk factors for the occurrence of milk fever. Therefore, dairy farm owners should be aware of the disease and prepare themselves how to manage peripartum intake of calcium. DOI: http://dx.doi.org/10.3329/ijns.v2i4.13287 International Journal of Natural Sciences (2012), 2(4) 104-107